2009
DOI: 10.1245/s10434-009-0590-6
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Imbalance at p53 and Microsatellite Instability Are Predictive Markers for Resistance to Chemotherapy in Gastric Carcinoma

Abstract: Background-Combined treatment with 5-fluorouracil and cisplatin (FP chemotherapy) is an effective neoadjuvant regimen for gastric carcinoma. However, it is ineffective in half of all patients. This study tests the hypothesis that genetic markers might identify those patients with gastric cancer who would respond to neoadjuvant FP chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Another commonly mutated gene which is linked to sensitivity to chemotherapy in gastric cancer is TP53 [ 85 ]. Eight examples of TP53 mutation including two stop codons are seen in the dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Another commonly mutated gene which is linked to sensitivity to chemotherapy in gastric cancer is TP53 [ 85 ]. Eight examples of TP53 mutation including two stop codons are seen in the dataset.…”
Section: Resultsmentioning
confidence: 99%
“…However, adjuvant chemotherapy is not the standard of care for stage II CRC in Germany, whereas stage III MSI CRCs clearly highly benefit from adjuvant chemotherapy. We could only find a single study investigating the effect of MSI on therapeutic response in GC 54. Herein, 23 patients in a randomized phase III trial were evaluated concerning their response to 5-fluoruracil and cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four full text articles were excluded for the following reasons. One was a conference abstract [11], seven duplicated data [12][13][14][15][16][17][18], one was a review article [19], one was an editorial comment [20], three investigated only the response to chemotherapy without gastrectomy [21][22][23], three reported no survival results [24][25][26], one failed to extract survival outcome [27], and seven reported no information about MSI [28][29][30][31][32][33][34]. To obtain the HR for one study [27] that we were unable to extract from the article for meta-analysis, we contacted the author by e-mail but received no reply.…”
Section: Included Studiesmentioning
confidence: 99%
“…All three reported that MSI tumors do not benefit from chemotherapy, and one study [56] reported that 5-FU-based chemotherapy was more effective in non-MSI gastric cancer. An additional three studies, which were not included in this meta-analysis, reported no difference in the responses of MSI and non-MSI tumors to chemotherapy [21][22][23]. If non-MSI gastric cancer responds favorably to chemotherapy, we can assume that the effect was offset; that is, MSI tumors were associated with a better prognosis, but did not benefit from chemotherapy, and non-MSI tumors were associated with a worse prognosis, but did benefit from chemotherapy.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%